Oral preparations
By using mucus hydrogel preparations that synthesize silica and PVA, the problem of tight bonding between teeth and gingival borders is solved, and the convenience of full transmission and removal of drugs is achieved.
Patent Information
- Application Number
- CN202210026652.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-03-11
- Filing Date
- 2017-01-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2037-01-12
AI Technical Summary
The prior art is difficult to achieve close bonding at the boundary parts of the teeth and gums, resulting in insufficient drug delivery and inconvenient removal.
A mucus hydrogel containing synthetic silica is used as the formulation, and hydrogen bonding of the –OH group of PVA and salts is formed to form a state of high elasticity and shape variability, ensuring the close bond of the formulation at the boundary parts of the teeth and gums.
It achieves high tight bonding force at the boundary of teeth and gums, ensuring sufficient contact time for the drug, and is free of irritation when removed, making it simple and convenient.
Smart Images

Figure CN114306214B_ABST
Abstract
Description
[0001] This application is a divisional application of PCT international application PCT / KR2017 / 000409, whose application date is January 12, 2017. The original application is an invention patent application. The application number entering the Chinese national phase is 201780006327.1, and the name is "Oral Preparations". Technical Field
[0002] This application claims the benefit of priority based on Korean Application No. 10-2016-0012964 filed on February 2, 2016, Korean Application No. 10-2016-0004353 filed on January 13, 2016, and Korean Application No. 10-2016-0029820 filed on March 11, 2016, and all the contents disclosed in the specifications and drawings of these applications are incorporated into this application in their entirety.
[0003] The present invention relates to a mouth band that is attached to teeth or the periphery of teeth to deliver a medicinal ingredient into the oral cavity. More specifically, the present invention relates to a mouth band that has excellent tight bonding force and ensures a sufficient attachment time to effectively deliver the medicinal ingredient into the oral cavity. Background Art
[0004] When delivering oral active ingredients to the oral cavity, the contact time with the active ingredient and the amount delivered play an important role.
[0005] Paste-like dosage forms such as toothpaste have insufficient viscosity and high solubility, so they cannot provide sufficient contact time with the target site. Mouth trays for the purpose of delivering drugs into the oral cavity have a strong foreign body sensation and are difficult to achieve local drug delivery due to their shape characteristics. Patches or strips are too thin to achieve sufficient delivery of active ingredients, and have reduced flexibility and are difficult to fit tightly between teeth and at the border between gums and teeth.
[0006] In order to solve the problem of close bonding between teeth, gums and tooth boundaries, Korean Patent No. 10-0623859 discloses a tooth whitening component delivery system using in-situ gel technology, but it has the disadvantage of strong fluidity when applied to the tooth surface and requires the use of other backing films. In addition, WO 2003 / 037276 discloses a preparation with low initial viscosity and applied to the oral cavity in a spray form, but due to the small difference between the general storage temperature (especially in summer) and the temperature in the oral cavity, if it is not applied very thinly, a rapid phase change cannot occur, resulting in the problem of difficulty in removal.
[0007] US 5,989,569 discloses coating a drug on the surface of a strip and delivering the drug by pressure. However, since the drug is coated on the surface of the strip and directly attached to the teeth, it has the effect of temporarily expelling the active ingredients, and there is a problem that it may cause strong irritation to the gums around the teeth. In addition, the physical properties of the strip and the coated drug, especially the softness, are different, so there is a disadvantage that it is difficult to adhere closely to the gap between teeth.
[0008] The inventors of the present invention have conducted research for many years to develop a new formulation that is easy to use and effectively delivers drugs to the oral cavity, and have proposed the present invention. In particular, efforts have been made to consider a formulation that has a high degree of adhesion even between teeth or curves and is suitable for use under special conditions in the oral cavity. Summary of the invention
[0009] Technical issues
[0010] In order to solve the above-mentioned problems, the present invention provides a novel oral adhesive preparation that can be easily applied to a desired part in the oral cavity and can ensure a sufficient contact time.
[0011] The present invention provides a preparation that can change shape before use and can be well and tightly attached to the gaps between teeth or between teeth and gums.
[0012] The preparation of the present invention provides a new form of preparation that does not flow down when initially applied, can be well and tightly adhered to the teeth and gaps between teeth in addition to the tooth surface and the tooth-gum boundary, and can be removed from the teeth without irritation when removed after sufficient drug release.
[0013] The present invention provides a novel oral preparation which is soft and flexible, does not flow and is easy to use, and can ensure a sufficient contact time with a target site.
[0014] Means of solving the problem
[0015] The present invention provides a preparation for adhesion to teeth or the area surrounding teeth.
[0016] In one embodiment of the present invention, the preparation for sticking on teeth or the peripheral part of teeth may be provided in the form of a mouth patch.
[0017] The preparation for sticking on teeth or tooth peripheral areas according to one embodiment of the present invention is stuck in the oral cavity in the form of a slime hydrogel containing synthetic silica.
[0018] The "mouth patch" used in this specification may refer to a dosage form that can be attached to teeth, gums, or buccals in the oral cavity. As an example, it can be attached in the form of a tape. The above-mentioned mouth patch can be formed into, for example, a rectangular shape, a circular shape, etc., and can be made into various shapes based on the attachment time to the target part as the target. If necessary, it can also be provided in the form of a dough such as clay without a specific shape.
[0019] The inventors of the present invention have conducted long-term research on an oral preparation that can easily change its shape with a small pressure so as to deliver a drug to the gaps between teeth and has an adhesion force and shape retention force to a degree that does not flow down at the adhesion site, and finally completed the present invention.
[0020] The term "slime hydrogel" used in this specification is used as a term to refer to a hydrogel that has excellent elongation and is easily stretched. The hydrogel forms a three-dimensional polymeric network and has swellability. It has the ability to absorb fluids and release drugs at a certain concentration. However, the hydrogel is stiff, so it is difficult to tightly adhere to the curves or gaps of teeth, and it may be easily broken when the hydrogel is stretched.
[0021] Mucus hydrogel is a new dosage form that has excellent softness like gel, is easily elongated, forms a three-dimensional polymer grid structure, has excellent drug release regulation, and can be freely deformed.
[0022] In one embodiment of the present invention, the mucus hydrogel may be a state having higher elasticity and shape variability than a state forming a three-dimensional network through hydrogen bonding between -OH groups of PVA and salts (e.g., borate). Mucus hydrogel is a dosage form having lower fluidity than slime and shape fixing force, but higher flexibility than hydrogel and the property of being easily elongated, and may have a shape variability intermediate between mucus and hydrogel.
[0023] In one embodiment of the present invention, the above mucus hydrogel dosage form can be achieved by synthetic silica or alginate compounds.
[0024] Silica is an inorganic thickener, which is very small, has a certain size, is water-insoluble, and has excellent dispersibility in aqueous solution. It has hydrogen bonding properties and can improve thixotropy, so it has an outstanding effect in realizing a mucus hydrogel dosage form, but the present invention should not be limited to these theories.
[0025] The synthetic silica can be any one or more selected from silica powder, fumed silica, precipitated silica, colloidal silica, aerogel, and silica sol. Preferably, fumed silica is used. The fumed silica can be made from, for example, EVONIK's For example, you can use 200, 300, etc. The synthetic silica may be contained in an amount of 0.1 to 20 wt %, preferably 0.5 to 10 wt %, based on the dry weight of the preparation for bonding to teeth or tooth peripheral areas.
[0026] When the content is within the above range, it is ideal from the perspective of rheology of the dosage form.
[0027] In one embodiment of the present invention, the polyvinyl alcohol (PVA) in the mucus hydrogel and the -OH group of the polyvinyl alcohol can form hydrogen bonds after reaction. The polyvinyl alcohol is a polymer that has proven biological stability and is a film-forming polymer that can form a very thin film. The -OH group contained in the polyvinyl alcohol forms a bridge structure gel through hydrogen bonds with salt, which has excellent elasticity, thereby achieving the dosage form characteristics targeted by the present invention by using it together with the synthetic silica of the present invention.
[0028] As the salt that forms a hydrogen bond with the -OH group of the above-mentioned polyvinyl alcohol, borate, phosphate or a mixture thereof can be used. The above-mentioned borate can include potassium borate, sodium borate, etc., and the above-mentioned phosphate can include tetrasodium pyrophosphate, tetrapotassium pyrophosphate, etc.
[0029] Preferably, considering the compatibility with the above-mentioned PVA and synthetic silica, the above-mentioned salt may be sodium borate.
[0030] A preparation according to another embodiment of the present invention is a mucus hydrogel comprising an alginate compound, which can be adhered in the oral cavity.
[0031] It has been confirmed that the hydrogen bonding properties of the alginate compound affect the formation of mucus hydrogel, so it shows an excellent effect in obtaining a dosage form that imparts thixotropy to the mucus hydrogel, but the present invention should not be limited to these theories. Preferably, the alginate compound is contained in an amount of 0.1 wt % to 20 wt % relative to the dry weight of the preparation, preferably 5 wt % or less, more preferably 2 wt % or less, and most preferably 0.5 wt % or less, so that the mucus hydrogel can be uniformly formed.
[0032] The alginate compound may include calcium alginate, potassium alginate, sodium alginate, triethanolamine alginate or a mixture thereof.
[0033] The preparation of the present invention may contain a medicinal ingredient that can be delivered into the oral cavity. The medicinal ingredient may include all medicinal ingredients that can be delivered into the oral cavity, preferably, a medicinal ingredient for the purpose of treating, preventing or improving oral diseases.
[0034] The above-mentioned medicinal ingredients may include, for example, teeth whitening ingredients, anti-caries ingredients including a fluoride ion supply source, plaque inhibition ingredients, anti-inflammatory ingredients, antibacterial ingredients, other vitamins, mineral ingredients, etc. In addition, ingredients for improving hypersensitive teeth and relieving symptoms may be included. More specifically, for example, it may include any one or more fluoride ion supply sources selected from the group consisting of sodium fluoride, stannous fluoride, indium fluoride, amine fluoride and sodium monofluorophosphate; a remineralization agent including hydroxyapatite; and as a tooth whitening component, it may include hydrogen peroxide, carbamide peroxide, calcium peroxide, perborate, percarbonate, peroxyacids, persulfates, calcium chlorite, barium chlorite, magnesium chlorite, lithium chlorite, sodium chlorite or a mixture thereof. In order to improve the whitening effect, condensed phosphates may be used at the same time. Phosphate) and peroxide, as the condensed phosphates that can be used, one or more of tetrasodium pyrophosphate (TSPP), sodium acidpyrophosphate (SAPP), sodium tripolyphosphate (STP), sodium potassium pyrophosphate, tetrapotassium pyrophosphate, acid sodium metaphosphate, and acid sodium polyphosphate can be used together with the above peroxide. Such condensed phosphates can also be used to remove dental plaque or inhibit dental plaque formation. And, these are chelating agents, which help to improve the whitening effect by removing metals that affect the formation of tooth stains.The invention may include: an antibacterial agent selected from the group consisting of triclosan, chlorhexidine, alexidine, hexetidine, sanguinarine, benzalkonium chloride, salicylanilide, domiphen bromide, cetylpyridinium chloride (CPC), tetradecylpyridinium chloride (TPC), or a mixture thereof; an anti-inflammatory agent selected from the group consisting of aspirin, ketorolac, flurbiprofen, piroxicam, meclofenamic acid, or a mixture thereof; or thiamine, riboflavin, nicotinic acid, pantothenic acid, or a combination thereof. acid), pyridoxine, biotin, folic acid, vitamin B12, lipoic acid, ascorbic acid, vitamin A, vitamin D, vitamin E, vitamin K, or a mixture thereof; or a mixture thereof, but not limited thereto. In addition, as a drug effective for the prevention and improvement of periodontal disease, it may include corn unsaponifiable quantitative extract, magnolia bark extract, myrrh, rubus, chamomile, polyphenol sulfonate, Centella asiatica quantitative extract, nutmeg extract, dexpanthenol, β-sitosterol, acetyl salicylic acid, etc., alone, or a mixture thereof in a certain proportion. As components for improving and alleviating the symptoms of hypersensitive teeth, one or two or more of zinc chloride, potassium phosphate, potassium pyrophosphate, calcium chloride, oxalic acid, potassium oxalate, ferric oxalate, etc. may be contained.
[0035] The above-mentioned medicinal ingredient may be present in a form dispersed uniformly or non-uniformly in the mucus hydrogel of the preparation.
[0036] The preparation according to one embodiment of the present invention may also contain a substance that helps release the active ingredient dispersed in the mucus hydrogel. For example, as the substance that helps release the drug, a substance that forms pores or a porous structure or bubbles (foam) in the dosage form may be used. For example, it may contain any one selected from i) acetic acid, lactic acid, malic acid, gluconic acid, ascorbic acid and other acids or their water-soluble salts, such as sodium citrate, and ii) sodium hydroxide (NaOH), potassium hydroxide (KOH), sodium bicarbonate (baking soda), sodium carbonate and other groups containing bases. Preferably, acetic acid is selected as the acid and sodium bicarbonate is selected as the salt. More preferably, the acid and salt mainly used in toothpaste, i.e., sodium citrate and sodium bicarbonate, may be selected.
[0037] The preparation according to one embodiment of the present invention may be present as a mucus hydrogel itself, or in a form where a support (e.g., a water-insoluble film) is attached to the preparation. When attached to teeth or the periphery of teeth, a backing film may be included as needed.
[0038] During the application of the preparation according to one embodiment of the present invention, there is a possibility that the preparation may come into contact with an unnecessary part, so the backing film may also play a role in preventing the preparation from coming into contact with the unnecessary part. The backing film may include a water-insoluble polymer generally used as an oral film, for example, polyethylene (PE), polypropylene (PP), ethylene-vinyl acetate copolymer (EVA), cellulose acetate phthalate, shellac, polyvinylacetate, ethyl cellulose, polymethyl methacrylate, methacryloylethyl betain / methacrylate copolymer (Yukaformer: manufactured by Mitsubishi, methacryloylethyl betain / methacrylate copolymer), methacrylic acid copolymer (Eudragit L 100, Eudragit L 12,5, Eudragit L 100-55, Eudragit L 30D-55), aminoalkyl methacrylate copolymer (Eudragit E 100, Eudragit E 30D-55), and the like. 12,5, Eudragit RL 100, Eudragit RL 30D), etc.
[0039] The term "teeth peripheral area" used in this specification generally refers to a concept that includes a part called gums, and can be used to mean a mucosal part that includes the teeth peripheral area. The teeth peripheral area can mean a part that includes a drug active ingredient that is delivered to the teeth and the oral cavity at the same time when the preparation is applied to the teeth due to the structure of the preparation. In this specification, teeth or teeth peripheral areas are collectively referred to as "teeth", and even if they are simply recorded as "teeth", they can be interpreted as including teeth or teeth peripheral areas in this specification.
[0040] In one embodiment of the present invention, when the drug of the preparation is released and removed from the teeth, it can be easily removed, and almost no residue is left on the surface. When synthetic silica is included according to one embodiment of the present invention, it is mixed with polyvinyl alcohol and sodium borate, so that the close bonding force to the teeth can be improved. In addition, when it is removed after the drug is released, no stickiness is left on the tooth surface, and it can be easily removed.
[0041] As another embodiment of the present invention, the present invention provides an oral preparation for sticking on teeth or tooth peripheral parts, comprising a phase transfer compound and a polymer that can adjust the hardening speed of the phase transfer compound after mixing with the phase transfer compound. The above-mentioned preparation can contain a medicinal ingredient that can be delivered to the oral cavity. After the above-mentioned preparation is stuck on the teeth or tooth peripheral parts, the active ingredient contained in the above-mentioned preparation can be released and delivered to the target part in the oral cavity.
[0042] Generally, in a phase transfer dosage form, when the phase transfer occurs after the first and second doses meet, they exist as a fixed block. The inventors of the present invention have confirmed that when the components for adjusting the phase transfer rate used in the present invention are used simultaneously, by adjusting the hardening rate of the phase transfer compound, a new form of preparation that effectively adjusts drug release can be provided, thereby completing the present invention.
[0043] The inventors of the present invention conducted long-term research to develop a new form of preparation that is easy to use and can effectively deliver a drug into the oral cavity, and finally proposed the present invention.
[0044] In the existing phase transfer dosage form, after the phase transfer is completed, it generally becomes a block and is removed by peeling (peel-off). If the phase transfer rate regulating substance according to an embodiment of the present invention is used at the same time, it is not a block when removed, and can have a structure in which smaller blocks are agglomerated together by weaker bonds, so that it can be removed by brushing (brush-off) in the manner of brushing teeth with a toothbrush. That is, it has the characteristics of removing the preparation of the present invention from the tooth surface by brushing teeth, and at the same time, the oral cavity is clean after use.
[0045] The term "teeth peripheral area" used in this specification generally refers to a concept that includes a part called gums, and can be used to mean a mucosal part that includes the teeth peripheral area. The teeth peripheral area can mean a part that includes a drug active ingredient that is delivered to the teeth and the oral cavity at the same time when the preparation is applied to the teeth due to the structure of the preparation. In this specification, teeth or teeth peripheral areas are collectively referred to as "teeth", and even if they are simply recorded as "teeth", they can be interpreted as including teeth or teeth peripheral areas in this specification.
[0046] The term "preparation" as used herein refers to a product that has been processed so as to fully exert the therapeutic effect without affecting the effect of the medicinal ingredient.
[0047] As used herein, "applying to teeth" may include the period from after the preparation of the present invention is placed on the teeth or the peripheral part to before the user applies pressure to tightly bond the preparation to the teeth.
[0048] As used herein, "when the preparation is tightly bonded to the teeth" means the moment when the user applies pressure to tightly bond the preparation to the tooth curves, tooth gaps, and between teeth and gums after a certain period of time has passed since the preparation was applied to the teeth.
[0049] The "moment of removing the preparation" used in this specification may refer to the moment when the preparation is tightly attached to the teeth or the surrounding tissues of the teeth, the drug is released, and the preparation falls off in the oral cavity. Depending on the purpose and use of the preparation and the amount of drug released, the preparation may be removed after two hours of sticking. However, in consideration of the ease of use, the preparation may be removed within 30 minutes after being tightly attached to the teeth, and more preferably within 10 minutes. The hardness of the preparation at the moment of removal may be increased compared to the moment when the preparation is applied to the teeth and the moment of tight attachment.
[0050] The term “adjusting the phase transfer rate” used in this specification can be used in the same sense as adjusting the hardening rate or degree of hardening of the preparation, and means that the degree of hardness of the preparation due to phase transfer over time can be adjusted.
[0051] The inventors of the present invention have repeatedly studied a drug delivery system capable of delivering a medicinal ingredient into the oral cavity, and finally proposed a new form of drug delivery system and a new method for delivering a medicinal ingredient into the oral cavity using such a system.
[0052] The inventors of the present invention have long studied new drug delivery systems that can effectively deliver active ingredients to specific parts of the oral cavity (e.g., parts that require teeth whitening, parts with hypersensitive teeth, parts with oral inflammation, parts with periodontal disease, etc.). As a result, a new form of oral preparation has been developed that can be easily applied to teeth or oral mucosa parts, and can be well adhered to curved parts and tooth gaps, thereby improving the drug delivery rate to the desired parts.
[0053] The dosage form that is most suitable for delivering drugs to the gaps between teeth is generally considered to be in a liquid form or a form with high fluidity. However, since the initial viscosity is very low and it is easy to flow down, it is inconvenient to use. In addition, there is a problem that the time of close adhesion to the target site is short and sufficient contact time cannot be ensured.
[0054] In order to solve such problems, a dosage form has been developed that is pasted on teeth and target parts in the oral cavity in the shape of dough, thereby improving the initial tight bonding force and not easy to flow down. Furthermore, the inventors of the present invention have confirmed through experiments that when a polymer with strong adhesion to the gums and teeth in the oral cavity and the property of participating in the phase transfer mechanism is mixed with a phase transfer compound, the deviation between the viscosity during initial use and the viscosity during removal is not large, so it is easy to stick and can be removed without irritation, thereby developing a new form of preparation.
[0055] As used herein, "applying to teeth" may include the period from after the preparation of the present invention is placed on teeth or peripheral areas to before the user applies pressure to tightly bond the preparation to the teeth.
[0056] The term "when the preparation is tightly bonded to the teeth" of the present invention refers to the moment when the preparation is tightly bonded to the tooth curve, tooth gap, or between the teeth and gums by the user applying pressure after a certain period of time has passed since the preparation was applied to the teeth.
[0057] The "moment of removing the preparation" of the present invention may refer to the moment when the preparation is tightly bonded to the teeth or the surrounding tissues of the teeth, the drug is released, and the preparation falls off in the oral cavity. Depending on the purpose and use of the preparation and the amount of drug released, the preparation may be removed after two hours of sticking. However, in consideration of the ease of use, the preparation may be removed within 30 minutes after being tightly bonded to the teeth, and more preferably within 10 minutes. The hardness of the preparation at the moment of removal may be greater than that at the moment when the preparation is applied to the teeth or at the moment of being tightly bonded.
[0058] In one embodiment of the present invention, the preparation of the present invention may include a polymer that adjusts the hardening speed of the phase transfer compound. The preparation according to one embodiment of the present invention includes a polymer that adjusts the hardening speed of the above-mentioned phase transfer compound, so that an oral preparation having an initial hardness that is convenient for use can be provided, and at the time of needing to be removed after the release of the drug, the hardness value is relatively low, easy to remove, and can reduce irritation to the adhesive site.
[0059] For example, alginate powder in a phase transfer compound hardens rapidly at the initial stage when in contact with water, and the hardness increases significantly over time, so that the active ingredients dispersed in the preparation cannot be released smoothly. However, in one embodiment of the present invention, a preparation prepared by mixing a polymer having a plurality of reactive groups, i.e., carboxyl groups, which are the same as alginate, such as a PVM / MA (Gantrez) polymer, does not undergo a sharp change in hardness, which is conducive to the release of the drug.
[0060] "Hardness" as used in this specification may indicate the degree of force required to compress the formulation. The hardness of the formulation of the present invention is measured using the compression test mode of the Stable Micro System TA XT Plus. After filling a 50 mL beaker with 20 g, a 20 mm diameter aluminum probe for measuring hardness is set, and the hardness is measured at a test speed of 1.5 mm / s and a target mode of 10 mm distance. The hardness can be understood as the peak value of the first cycle calculated. Its unit is g (g-force).
[0061] The phase transfer substance is a substance that can cause the viscosity of the oral composition, and can be used alone: carrageenan, pectin, xyloglucan, gellan gum, ammonium alginate, magnesium alginate, potassium alginate, sodium alginate, lithium alginate, chitosan, poly (D, L-lactic acid), poly (DL-lactide-co-glycolide), poly-caprolactone, polyacrylic acid (carbopol), polyvinylacetal diethyl aminoacetate (AEA), hydroxypropylmethylcellulose (hydroxypropylmethylcellulose), etc. cellulose), poly(methacrylicacid)-poly(ethylene glycol), poly(D,L-lactide)-b-poly(ethylene glycol)-b-poly(D,L-lactide), PEG-oligoglycolyl-acrylate, poly(N-isopropyl acrylamide), sucrose acetate isobutyrate, polyvinyl alcohol, polyvinyl acetate, glyceryl oleate, glyceryl monolinoleate, glyceryl monoarachidonate, glyceryl monostearate Monostearate), etc., or a mixture of two or more thereof, and all substances used as phase transfer substances in the art can be used, and are not limited to the above examples.
[0062] Preferably, the phase transfer compound may be ammonium alginate, magnesium alginate, potassium alginate, sodium alginate, lithium alginate or a mixture thereof.
[0063] The phase transfer compound may be included in the formulation together with a polymer having the property of adjusting the hardening speed of the phase transfer compound. The polymer having the property of adjusting the hardening speed of the phase transfer compound may contain the same functional group (e.g., carboxyl group) as the functional group contained in the phase transfer compound.
[0064] The polymer having the characteristic of adjusting the hardening speed of the phase transfer compound contained in the preparation of the present invention may include any one or more of a plurality of polymers selected from functional groups such as carboxyl and hydroxyl groups that participate in the phase transfer mechanism of the phase transfer compound. For example, when the preparation of one embodiment of the present invention performs a phase transfer reaction brought by alginic acid and its salt, the polymer may be selected from a polymer having a carboxyl group, such as polyacrylic acid, sodium polyacrylate, carbomer, Cabopol, acrylic copolymer (Acrylate copolymer) (Eudragit L-100), polyquaternium-39, methyl vinyl ether and maleic anhydride copolymer (PVM / MA copolymer) Any one or more polymers of the group consisting of. Preferably, the polymer can utilize Gantrez as one of methyl vinyl ether and maleic anhydride copolymers, and most preferably, it can utilize grade, i.e. Gantrez S-97, which is water-soluble and applicable to oral products. The above polymers have excellent adhesion to teeth and gums and can be well used for the purpose of the present invention. On the contrary, when a phase transfer reaction based on polyvinyl alcohol is performed, a polymer having a hydroxyl group, such as polyethylene glycol, hyaluronic acid salt, microcrystalline cellulose hydroxypropylmethylcellulose, methylcellulose, alginic acid, or one or more of carrageenan can be used.
[0065] It is considered that the polymer having the property of adjusting the curing rate of the phase transfer compound inhibits the bonding of the phase transfer compound with water-soluble calcium, and the carboxyl group (-COOH) contained in the polymer binds with water-soluble calcium to inhibit the curing of the phase transfer compound, but the present invention is not limited to this theory.
[0066] Preferably, the polymer having the property of regulating the hardening speed of the phase transfer compound is water-soluble and may contain the same functional groups as those contained in the phase transfer compound. For example, the -COOH group contained in PVM / MA binds to water-soluble calcium, hindering the binding of alginate to water-soluble calcium, thereby delaying hardening.
[0067] The polymer having the property of adjusting the phase transfer reaction rate may contain 0.01% to 10% by weight relative to the total weight of the preparation, preferably, 0.05% to 5% by weight. When in contact with water within the above range, it can have the hardness range targeted by the present invention, and can provide excellent tight binding force. In addition, when the content ratio of the above polymer exceeds the above range, the binding with the phase transfer compound is strong, which may affect the release of the dispersed active ingredients and sometimes hinder the release of the active ingredients. The above phase transfer compound and the polymer having the property of adjusting the phase transfer reaction rate are mixed in a weight ratio of 5:0.01 to 0.07 of the phase transfer compound: the polymer having the property of adjusting the phase transfer reaction rate, preferably, in a weight ratio of 5:0.03 to 0.05. Within the above weight ratio range, the hardness of the preparation targeted can be obtained.
[0068] The above-mentioned medicinal ingredients may be uniformly dispersed in the oral composition, and even if they are not uniformly dispersed, they may be included in the mixture of the present invention.
[0069] According to one embodiment of the present invention, the preparation of the present invention also has a semi-solid property, so it can be tightly bonded to a bend or gap.
[0070] The preparation of the present invention may be in the form of dough or clay, and may be applied to teeth or areas surrounding teeth in the form of an ointment.
[0071] In one embodiment of the present invention, the above-mentioned preparation can be in two dosage forms, and can also be in three dosage forms as required. For example, i) one dosage form containing a phase transfer compound and two dosage forms containing a polymer for adjusting the phase transfer reaction rate, water, a pharmacological ingredient, and a component that can be included in other preparations can be mixed and used, and ii) one dosage form containing a phase transfer compound; two dosage forms containing a polymer for adjusting the phase transfer reaction rate; and three dosage forms containing water, a pharmacological ingredient, and a component that can be included in other preparations can also be mixed and used.
[0072] The first and second agents, or the first, second and third agents, may be mixed and then applied to the teeth or the peripheral areas of the teeth.
[0073] According to another embodiment of the present invention, the following preparation for adhesion to teeth or the peripheral part of teeth is provided: it contains a phase transfer compound and a polymer, after the polymer is mixed with the above-mentioned phase transfer compound for 1 minute, the hardness of the preparation reaches 140g to 350g, and after mixing with the above-mentioned phase transfer compound for 10 minutes, the hardness of the preparation reaches 5,200g to 13,000g, and the preparation for adhesion to teeth or the peripheral part of teeth delivers the medicinal ingredients contained in the preparation to the oral cavity.
[0074] As the phase transfer compound, any substance that induces viscosity as defined in the present specification may be used. Preferably, carrageenan, pectin, xyloglucan, gellan gum, ammonium alginate, magnesium alginate, potassium alginate, sodium alginate, lithium alginate, chitosan, poly(D,L-lactic acid), poly(DL-lactide-co-glycolide), poly-caprolactone, polyacrylic acid (carbopol), polyvinylacetal diethylaminoacetate (AEA), hydroxypropylmethylcellulose (hydroxypropylmethylcellulose) are used alone. cellulose), poly(methacrylic acid)-poly(ethylene glycol), poly(D,L-lactide)-block-poly(ethyleneglycol)-block-poly(D,L-lactide), PEG-oligoglycolyl-acrylate, poly(N-isopropyl acrylamide), sucrose acetate isobutyrate, polyvinyl alcohol, polyvinyl acetate, glyceryl monooleate, glyceryl monolinoleate, glyceryl monoarachidonic acid Monoarachidonate), glyceryl monostearate, or two or more thereof may be used together. All substances used as phase transfer substances in the art may be used, and the phase transfer substances are not limited to the above examples.Preferably, the phase transfer compound is alginic acid or a salt thereof. Preferably, the alginic acid or a salt thereof is ammonium alginate, magnesium alginate, potassium alginate, sodium alginate, lithium alginate or a mixture thereof.
[0075] In order to effectively release the active ingredients contained in the preparation containing the above-mentioned phase transfer compound and tightly bind to the teeth, tooth gaps or surrounding tissues of the teeth, the above-mentioned preparation needs to have a viscosity and hardness that is easy to operate within 1 minute after mixing 1 and 2 doses. Preferably, it is easy to operate when it has a hardness of 140g to 350g. In addition, 10 minutes after the ingredients of the mixed preparation are released, the drug can be smoothly released. In order to maintain the shape fixing force and adhesive force, it is easy to operate when it has a hardness of 5,200g to 13,000g. In order to provide the hardness of the preparation targeted by the present invention, it is preferred that it can contain any one or more of the group consisting of polyacrylic acid, sodium polyacrylate, carbomer, carbopol, acrylic copolymer (Eudragit L-100), polyquaternium-39 and copolymer of methyl vinyl ether and maleic anhydride (PVM / MA copolymer). Preferably, the above-mentioned polymer can be a copolymer of methyl vinyl ether and maleic anhydride (PVM / MAcopolymer).
[0076] The shape-fixing force that can be achieved by the preparation of the present invention can ensure sufficient contact time with the area where the drug is required, and is therefore more conducive to achieving the target effect.
[0077] According to an embodiment of the present invention, the difference between the hardness measured after 1 minute of mixing and the hardness measured after 10 minutes is 5,000 g to 12,000 g, preferably 6,000 g to 10,000 g. When the difference in hardness is within the above range, it is easy to stick, so it is convenient to handle, and the release of the drug is more effective and easy to remove, so it is more conducive to achieving the purpose of the present invention.
[0078] The preparation of the present invention may also contain a substance that helps release the above-mentioned drug. As the substance that helps release the above-mentioned drug, all substances that form pores or porous structures or bubbles (foam) in the dosage form can be used. For example, when it is composed of two types of 1 dose and 2 doses, when the two dosage forms of 1 dose containing acid and 2 doses containing alkali meet to form a viscous shape, bubbles are formed in the dosage form. That is, 1 dose contains acetic acid, lactic acid, malic acid, gluconic acid, ascorbic acid, etc. or their water-soluble salts, such as sodium citrate, and 2 doses can be any one selected from the group of alkalis such as sodium hydroxide (NaOH), potassium hydroxide (KOH), baking soda, sodium carbonate, etc. Preferably, acetic acid can be selected as the acid, and sodium bicarbonate can be selected as the salt. More preferably, the acid and salt mainly used in toothpaste, i.e. sodium citrate and sodium bicarbonate, can be used.
[0079] The preparation of the present invention is obtained by mixing dose 1 and dose 2, and the phase transfer compound comes into contact with water, thereby gradually increasing its hardness and being easily adhered to teeth. At the time of removal, the hardness is lower than the hardness range of general phase transfer compounds when they meet water, and the preparation has a shape fixing force, so when removed, it will not cause irritation to teeth and gums.
[0080] Another embodiment of the present invention provides a preparation for sticking to teeth or the peripheral part of teeth, comprising i) a pharmaceutical ingredient, ii) a phase transfer compound, and iii) a polymer that is insoluble in water and soluble in ethanol. The preparation of the present invention is applied to teeth or the peripheral part of teeth in a liquid state, and after application, it comes into contact with saliva in the oral cavity, undergoes phase transfer, and has adhesion to teeth or the peripheral part of teeth.
[0081] As a solvent for manufacturing the above-mentioned preparation, ethanol is used. The preparation of the present invention contains a polymer that is completely insoluble in water or is soluble in water under certain conditions (for example, a certain ratio of water to ethanol (for example, the content of ethanol in a mixture of ethanol and water is more than 80%) or a certain pH condition), but is soluble in ethanol. The above-mentioned preparation may contain the above-mentioned polymer that is insoluble in water and soluble in ethanol. The above-mentioned polymer that is insoluble in water and soluble in ethanol may include a polymer that is insoluble in water at a temperature of 35 to 38° C. and pH 7, but is soluble in ethanol.
[0082] The above-mentioned preparation provides excellent ductility when applied to teeth or the area surrounding teeth, and can have adhesion to teeth or the area surrounding teeth after a certain period of time in the oral cavity.
[0083] The inventors of the present invention have experimentally confirmed that the ingredients contained in the preparation induce phase transition after contact with saliva, and at the same time, a polymer that is insoluble in water and soluble in ethanol is used. Therefore, even if the target area is loaded with a lot of loading and coated thickly, the preparation will harden quickly and have sufficient adhesion to the target area in the oral cavity for a long time.
[0084] The solubility of the preparation of the present invention changes in a moist oral cavity, i.e., it dissolves in ethanol, which is the solvent of the preparation, and then, after coming into contact with a large amount of water (saliva) with a pH of less than 7 in the oral cavity, the solubility decreases, and the preparation can stay in the target area in the oral cavity for a sufficient time, thereby achieving the desired effect.
[0085] The preparation of the present invention is in a liquid form with excellent fluidity when it is just applied in the oral cavity, and can penetrate well into the gaps between teeth and the boundary between teeth and gums. After application, the preparation of the present invention reacts with saliva over time, and the preparation gradually hardens and becomes a gel, which is attached to the teeth or the peripheral part of the teeth.
[0086] The term "gelation" used in this specification means that in addition to the phenomenon of transformation from sol to gel, it also includes a significant increase in elasticity or a phenomenon accompanied by an increase in viscosity. It includes the phenomenon that the liquid hardens after contact with saliva, and the degree of increase in elasticity or viscosity through gelation is not particularly limited.
[0087] The phase transfer compound may include any one of monoglycerides selected from glyceryl monooleate, glyceryl monolinoleate, glyceryl monoarachidonate, glyceryl monostearate or a mixture thereof. Preferably, glyceryl monooleate and / or glyceryl monolinoleate may be used.
[0088] In view of the object of the present invention, preferably, the above-mentioned phase transfer compound is a monoolein that causes phase transfer after contact with moisture. The above-mentioned phase transfer compound can be included in an amount of 5 to 80% by weight relative to the total weight of the preparation. In the above-mentioned content range, when contacted with a small amount of water or saliva, it has the characteristics of phase transfer, and therefore, it is more ideal in achieving the purpose of the present invention.
[0089] The preparation of the present invention also uses a polymer that is soluble only in ethanol and almost insoluble in water. The polymer that is soluble only in ethanol also changes from a soluble phase to an insoluble phase when in contact with water. Therefore, the polymer that is soluble only in ethanol also undergoes a phase transition in another sense, so the phase transition compound can be included in the preparation in the content range as described above.
[0090] The water-insoluble and ethanol-soluble polymer included in one embodiment of the present invention may include a) a polymer that is soluble in ethanol but a) insoluble in water, or b) a polymer that is generally insoluble in water but is soluble in water under specific conditions such as a pH higher than the pH in the oral cavity (pH7), for example, a common enteric coating polymer that is insoluble in the stomach under acidic conditions or in a dosage form under neutral conditions but is soluble only in the intestine under alkaline conditions. For example, it may include b) a polymer that is generally insoluble in water but is soluble in water under specific conditions such as conditions higher than the general oral pH and soluble in ethanol, and is insoluble in water below pH7.
[0091] Monoglyceride has the characteristic of undergoing phase transition according to temperature and water content, and has the characteristic of changing structural shape and physical properties with phase transition. When the above monoglyceride undergoes phase transition, it changes from a fluid structure to a non-fluid and adhesive solid structure. However, in order to make the monoglyceride phase transition quickly, it cannot be applied too thickly, so it is applied as thinly as possible to the desired target in a spray manner. Phase transfer preparations using monoglyceride are not suitable for delivering sufficient amounts of drugs in a very thin thickness, and are only used in preparations such as some deodorants that do not require sufficient adhesion time to deliver drugs.
[0092] The present invention solves such a problem and provides a solution that ensures a sufficient adhesion time and can effectively deliver drugs.
[0093] The polymer that is insoluble in water but soluble in ethanol may be ethyl cellulose, butyl ester of PVM / MA copolymer, polyvinylacetate, polyvinyl acetate phthalate, shellac, rosin, methacrylic acid copolymer (for example, L100, L100-55) or a mixture thereof, preferably, ethylcellulose, buthyl ester of PVM / MA copolymer or a mixture thereof.
[0094] In one embodiment of the present invention, preferably, the above-mentioned medicinal ingredient is a medicinal ingredient that is insoluble in water and only soluble in ethanol. In another embodiment, preferably, the above-mentioned medicinal ingredient is a medicinal ingredient that is not easily soluble in water but is uniformly dispersed in water.
[0095] According to another embodiment of the present invention, the preparation may have a viscosity similar to that of a solution or gel that normally flows down, for example, when measured by a Brookfield viscometer at room temperature with an RV6 rotor and a speed of 20, it has a viscosity of less than 10,000, preferably less than 5,000, further preferably, a viscosity of 100 to 10,000, and even more preferably, a viscosity of 500 to 5,000. The present invention provides, through an embodiment, a preparation for adhesion to teeth or the peripheral part of teeth, which has the above-mentioned viscosity range before meeting saliva, and after being applied to the teeth or the oral cavity, changes phase into a gel or solid that is adhesive to the teeth or the oral tissues. Preferably, the above-mentioned phase change can be measured under the temperature conditions in the oral cavity, preferably, under the temperature conditions of 36 to 38°C.
[0096] The viscosity can be measured by using a Brookfield viscometer commonly used in the art, with an RV6 rotor, at room temperature or oral temperature. The viscosity indicates the physical properties of viscosity, and viscosity and viscosity can be used together. The unit can be cPs.
[0097] The above-mentioned formulation may comprise the water-insoluble ethanol-soluble polymer of the present invention and the phase transfer compound of the present invention.
[0098] In one embodiment, the above-mentioned preparation may include a polymer selected from glyceryl monooleate, glyceryl monolinoleate, glyceryl monoarachidonate, glyceryl monostearate or a mixture thereof; and a polymer selected from ethyl cellulose, PVM / MA copolymer butyl ester, polyvinyl acetate, polyvinyl acetate-phthalate, shellac, rosin, methacrylic acid copolymer or a mixture thereof.
[0099] The term "teeth peripheral area" used in this specification generally refers to a concept that includes a part called gums, and can be used to mean a mucosal part that includes the teeth peripheral area. The teeth peripheral area can mean a part that includes a drug active ingredient that is delivered to the teeth and the oral cavity at the same time when the preparation is applied to the teeth due to the structure of the preparation. In this specification, teeth or teeth peripheral areas are collectively referred to as "teeth", and even if they are simply recorded as "teeth", they can be interpreted as including teeth or teeth peripheral areas in this specification.
[0100] The term "preparation" as used herein refers to a product that has been processed so as to fully exert the therapeutic effect without affecting the effect of the medicinal ingredient.
[0101] The term "applied to teeth" as used herein means that the preparation of the present invention is included in the term "applied" as long as it contacts the teeth or the peripheral area.
[0102] The inventors of the present invention have repeatedly studied a drug delivery system capable of delivering a medicinal ingredient into the oral cavity, and finally proposed a new form of drug delivery system and a new method for delivering a medicinal ingredient into the oral cavity using such a system.
[0103] When attached to teeth or the peripheral part of teeth, the preparation may further include a backing film as required. When the preparation according to one embodiment of the present invention takes a long time to harden, it may stick to unwanted parts such as gums, so the backing film may also play a role in preventing it from sticking to unwanted parts. The above-mentioned backing film can contain a water-insoluble polymer generally used as an oral film, for example, polyethylene (PE), polypropylene (PP), ethylene-vinyl acetate copolymer (EVA), cellulose acetate phthalate, shellac, polyvinyl acetate, ethyl cellulose, polymethyl methacrylate, methacryloylethyl betain / methacrylate copolymer (Yukaformer: manufactured by Mitsubishi, methacryloylethyl betain / methacrylate copolymer), methacrylic acid copolymer (methacrylic acid copolymer; Eudragit L 100, Eudragit L12,5, Eudragit L 100-55, Eudragit L 30D-55), aminoalkyl methacrylate copolymer (aminoalkyl methacrylate copolymer; Eudragit E 100, Eudragit E 12,5, Eudragit RL100, Eudragit RL30D), etc. can be used.
[0104] In one embodiment of the present invention, when the drug in the preparation is released and then removed, it can be simply removed with a toothbrush.
[0105] According to one application example, after the dough-like preparation of the present invention is coated on the backing film, it is attached to the target part in the oral cavity, and after a certain period of time (when it becomes hard and does not stick to the gums, etc.), the support can be removed. After removing the support, at the time of removal, the preparation of the present invention can be removed by brushing teeth with a toothbrush that is usually used. When using it in a peeling manner, the support is not removed in the middle of the hardening process, and can be removed together at the time of removal.
[0106] The preparation of the present invention can be removed by brushing (removal by brushing teeth) when it is removed from the teeth or the peripheral part of the teeth after a certain period of time. The preparation of the present invention can be removed by external stimulation similar to normal brushing teeth. The tool used for brushing can be, for example, a toothbrush, a sponge, etc., and its type is not particularly limited.
[0107] Effects of the Invention
[0108] According to the preparation of the present invention, a high adhesion force can be imparted to a desired site even between teeth or on a tooth curve.
[0109] When removing, no stickiness will be left on the tooth surface and it can be easily removed.
[0110] The preparation according to the present invention, such as chewing gum or dough, has excellent self-healing agglomeration properties, and is easy to handle while adjusting the drug release properties.
[0111] After sticking, the drug will not flow down or be diluted by saliva, and the contact time between the drug and the preparation of the present invention can be fully ensured, which is conducive to achieving the target efficacy.
[0112] When applied to teeth, it does not drip, so it is easy to use.
[0113] During the initial application, the hardness is relatively high and it is not easy to flow down, making it easy to handle. After a certain period of time after application, the increase in hardness is relatively small, making it easier to remove and reducing irritation to the area around the application.
[0114] Generally, oral preparations containing phase transfer substances need to be applied at a thin thickness to ensure sufficient contact time with the adhesive portion. However, according to the present invention, even if applied thickly, the solubility of the preparation changes rapidly (soluble -> insoluble) in the moist oral cavity, and sufficient contact time can be ensured. BRIEF DESCRIPTION OF THE DRAWINGS
[0115] Figure 1 PVM / MA (left side) which corresponds to an example of the polymer capable of adjusting the curing speed of the phase transfer compound of the present invention is shown, and the structure of the alginate-calcium complex (right side) is shown.
[0116] Figure 2 The hardness change of the preparation confirmed 1 minute after mixing the preparation is shown. The vertical axis unit is g. Figure 2 It can be seen that the hardness of the preparation of the example increases faster within 1 minute after mixing, and 1 minute later, the hardness of the example has a larger value than that of the comparative example. In other words, it can be seen that the preparation of the example is easier for the user to handle than that of the comparative example 1 minute after mixing.
[0117] Figure 3 The hardness change of the preparation confirmed from immediately before mixing to the time when 10 minutes have passed is shown. Figure 3 It can be seen that according to the example, the hardness of the preparation has a lower value than that of the comparative example at the time of 10 minutes. In other words, it can be seen that after a certain period of time after sticking, the comparative example hardens more firmly.
[0118] Figure 4 A diagram schematically illustrates the hardening process after the preparation is applied to the teeth and tightly bonded according to an embodiment of the present invention. Figure 3 It can be seen that the preparation of the present invention can reach the gaps between teeth.
[0119] T represents a tooth, and 10 represents a preparation for adhesion to a tooth or a tooth peripheral area. DETAILED DESCRIPTION
[0120] Below, in order to more specifically illustrate the present invention, the following examples etc. are described. However, various modifications may be possible according to the embodiments of the present invention, and it should not be construed that the protection scope of the present invention is limited to the embodiments described below. The embodiments of the present invention are provided schematically to help a specific understanding of the present invention. It should be understood that, in the absence of special instructions, the % recorded in this specification represents weight %.
[0121] [Manufacture of mouth patches and oral preparations]
[0122] Examples and comparative examples were produced as follows.
[0123] The following composition was prepared by setting the temperature to 50° C. and mixing with a mechanical mixer.
[0124]
Table 1
[0125]
[0126]
Table 2
[0127]
[0128] [Evaluation of the tight bonding strength between interproximal and buccal surfaces]
[0129] 1. Comparative experiment on the tight bonding between teeth and on the tooth surface (using the artificial tooth surface bacterial film removal method)
[0130] (1) Experimental methods
[0131] -Evaluation equipment: ITPlus 4.0Microcam
[0132] -Evaluation method: Comparison of the removal of bacterial film from the artificial tooth surface before and after the bonding of the comparative example and the example on the interdental space and the tooth surface by area
[0133] a) Method for coating artificial tooth surface bacterial film on artificial tooth model
[0134] The cheek side of the maxillary posterior teeth in the jaw model, where the toothbrush is easily applied, was immersed in a polymer (containing a red dye) for 10 seconds, taken out, dried at room temperature for 60 minutes, and then further dried in a drying room for 60 minutes, thereby producing an artificial tooth surface bacterial film.
[0135] b) Test method for tight bonding between teeth and on tooth surfaces
[0136] After a small amount of water was sprayed on the embodiments and comparative examples to form moist oral conditions, the artificial teeth coated with the artificial tooth surface bacterial film to be tested were tightly adhered and removed after 10 minutes. Thereafter, under the same conditions, the artificial tooth surface bacterial film in the interdental spaces and the front surfaces of the teeth was removed, and the areas between the teeth (interproximal) and the tooth surface (buccal surface) before and after adhesion were measured for comparison.
[0137] (2) Experimental results
[0138] The areas of artificial tooth surface bacterial film removed between teeth (teeth gaps) and tooth surfaces using the examples and comparative examples were measured. (A larger area of bacterial film removal indicates a higher bonding strength at that location)
[0139]
Table 3
[0140] area Example 1 Example 2 Comparative Example 1 Comparative Example 4 Teeth 30.01 28.90 25.80 10.55 Tooth surface 89.98 85.33 79.12 70.11
[0141] It can be seen from Table 3 that the bacterial film removal areas of the tooth gaps and tooth surfaces of Examples 1 and 2 are large. From the above results, it can be seen that Examples 1 and 2 have excellent ability to be closely bonded even to the tooth gaps, have low fluidity, and can ensure sufficient contact time with the tooth surface, thereby having excellent ability to remove bacterial film on the tooth surface.
[0142] [Shape retention and length expansion comparison experiment]
[0143] 1. Shape retention
[0144] After pasting the embodiment and comparative example on a complete oral tooth model consisting of the upper and lower jaws, the time when the shape could not be maintained and began to flow down was recorded to evaluate whether it had the physical strength to maintain the pasted shape during use. Using the tooth model, the upper jaw was pasted in a way that covered the boundary between about three teeth / gingiva, and it was observed for 10 minutes whether it flowed down to the lower jaw or remained pasted. After that, it was scored on a 5-point scale, with 5 points if the shape remained the same as the beginning, 4 points if it flowed down a little but the shape and position remained the same, 3 points if it flowed down and the shape and position deviated a little, 2 points if it deviated a lot, and 1 point if it was completely out of the pasted position.
[0145]
Table 4
[0146] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Shape retention 5 5 5 3 2 2 4
[0147] 2. Comparative test of tensile properties and ductility
[0148] For the examples having excellent shape retention in the above Table 4, length expandability experiments were also conducted.
[0149] Take Example 1g, place it on a PET sheet with a length of 1 cm*1 cm horizontally and vertically, and then place other PET sheets on it. The maximum length that can be expanded without being torn or having holes when pressed with fingers is measured and compared.
[0150]
Table 5
[0151] Example 1 Example 2 Example 3 Comparative Example 4 Expanded length 6 times 8 times 1.5 times Product status: No expansion when pressed
[0152] As can be seen from Table 5, the embodiment has excellent shape retention when attached to the tooth surface, and has excellent length expansion force and stretchable properties. In particular, Comparative Example 4 has no significant difference in shape retention from the embodiment of the present invention, but has the property of not expanding when pressed. Due to such differences, the preparation of Comparative Example 4 is difficult to completely and tightly adhere to the gap between teeth. However, the preparation of the present invention has complete tight adhesion including the curve or gap of teeth.
[0153] [Ease of use questionnaire for humans (adhesion, shape retention, tight bonding, removal, etc.)]
[0154] 1) Experimental subjects and usage method: A total of ten volunteers were used as subjects, and Examples 1 to 3 and Comparative Examples 1 to 4 were used alternately three times, and then a questionnaire survey was conducted using a 5-point Likert scale.
[0155] 2) Scale Standard
[0156] 5 points: Very satisfied
[0157] 4 points: quite satisfied
[0158] 3 points: Average level
[0159] 2 points: Somewhat dissatisfied
[0160] 1 point: Very dissatisfied
[0161] As a criterion, regarding the adhesion strength, when it is easy to stick to the desired position and stick at the sticking position until the desired sticking time, it is judged to have excellent adhesion strength. Regarding the shape retention strength, it is judged to have excellent shape retention strength when it does not flow down after sticking to the desired position and maintains the shape well. Regarding the tight adhesion strength, when the dosage form is easily and tightly attached to the gap between teeth or the tooth / gum boundary by lightly pressing with fingers, it is judged to have excellent tight adhesion strength. Regarding the removal strength, a questionnaire survey was conducted using the following 5-point Likert scale.
[0162] 5: It is very easy to remove and there is no residue on the teeth.
[0163] 4: Easy to remove, but leaves a little residue.
[0164] 3: It is inconvenient to remove, leaving residue and discomfort.
[0165] 2: It is inconvenient to remove and leaves a lot of residue.
[0166] 1: It is very inconvenient to remove and leaves a lot of residue.
[0167] 3) Experimental results
[0168]
Table 6
[0169] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Adhesion 4 4 4 4 4 2 2 Shape retention 5 5 5 3 2 2 4 Tight binding force 5 5 5 5 2 5 3 Removal force 5 5 5 4 2 4 2
[0170] As can be seen from Table 6, the Examples were able to obtain very excellent results in terms of adhesion overall, that is, the extent of dripping or migration after adhesion was less than that of the Comparative Examples.
[0171] In addition, good results were obtained in terms of close adhesion, but when the shape maintenance and adhesive strength were comprehensively considered, the example obtained a more excellent use feeling evaluation result.
[0172] [Clinical evaluation of improvement of hypersensitive teeth or gingivitis in humans]
[0173] 1) Experimental subjects and usage: For Examples 1 to 3 and Comparative Examples 1 to 4, apply the product to sensitive teeth or painful gums once a day for 10 minutes and then remove it.
[0174] 2) 15 volunteers from each group with hypersensitive teeth or gum pain were selected as subjects and evaluated by questionnaire using a 5-point Likert scale after using the product for one week.
[0175] 5 points: The improvement effect on sensitive teeth / gum pain lasts for one month in all the areas where the sticker was applied.
[0176] 4 points: The improvement effect of sensitive teeth / gum pain is clearly felt in all the sensitive teeth / gum pain areas where the patch was applied.
[0177] 3 points: The improvement effect of sensitive teeth / gum pain is clearly felt at one or more sensitive teeth / gum pain sites where the sticker is applied.
[0178] 2 points: The sensitivity of hypersensitive teeth to cold food or gum pain after ingesting food is reduced compared to before use.
[0179] 1 point: No improvement in hypersensitive teeth or gum pain was felt.
[0180] The following efficacy questionnaire results of the embodiments and comparative examples were obtained.
[0181]
Table 7
[0182] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Hypersensitive teeth improvement - - 4 - - 3 3 Gingivitis improvement 4 4 - 3 1 - -
[0183] As can be seen from Table 7, the mouth patch of the embodiment has a better effect in the oral cavity than the comparative example. The mouth patch of the embodiment has excellent tight adhesion to the target part in the oral cavity, and can deliver the drug to the gap between teeth, which is conducive to achieving the intended effect. In addition, sufficient contact time can be ensured, and the drug can be delivered simply.
[0184] [Manufacture of oral preparations]
[0185] Oral preparations of Examples and Comparative Examples having the following compositions were manufactured or purchased.
[0186] Examples and comparative examples were produced as follows.
[0187] According to the following composition, two doses were prepared while mixing with a mechanical mixer at 50° C. The content of the alginate powder mixed with the second dose was 100 times the weight of the second dose.
[0188]
Table 8
[0189]
[0190] [Hardness comparison experiment (experimental method: measured using a texture analyzer)]
[0191] -Evaluation equipment: Stable Micro System TA XT Plus
[0192] -Evaluation method: The hardness of the comparative examples and examples was measured using a texture analyzer.
[0193] The hardness was measured using a texture analyzer in the compression test mode of the texture analyzer TA (Texture Analyzer). 20 g of the examples and comparative examples were placed in a 50 mL beaker, and then an aluminum probe with a diameter of 20 mm for measuring hardness was set up, and the hardness was measured under the conditions of a test speed of 1.5 mm / s and a target mode of a distance of 10 mm. The hardness calculated by the device is the peak value of the first cycle.
[0194] - Experimental results
[0195] Table 9 shows the results of a comparative test on the hardness change over time after mixing the first and second doses of the examples and comparative examples described in Table 8.
[0196]
Table 9
[0197] Example 4 Example 5 Example 6 Comparative Example 5 Comparative Example 6 Comparative Example 7 After mixing (1 minute) 150 g 180g 340g 109g 120g 80g 3 minutes 260g 280g 810g 14,800g 180g 15,000g 5 minutes 2,400g 1600g 2,100g 21700g 5,000g 20,000g 10 minutes 12,000g 5,600g 5,400g 22600g 16,000g 22,400g
[0198] It can be seen from Table 9 that in the initial stage after mixing, the hardness value of the embodiment is larger and can be easily applied to teeth or processed. Until 10 minutes after mixing, the hardness does not change much. When removing, there is no irritation and it can be easily removed, which is easy to use. Figure 2 3 shows the hardness variation results according to the above-mentioned embodiment and comparative example in a graphical form.
[0199] [Test of feeling after use]
[0200] The use feeling test was conducted using the formulations having the composition shown in Table 8. Before use, mix the formulations 1 and 2, and then apply the mixture to the backing film. After applying the backing film to the desired part, press with your fingers to make it adhere tightly. The backing film may not be removed, but in this experiment, the backing film was removed after 2 minutes of application. It was removed after 10 minutes of application.
[0201] 1. Questionnaire survey on close integration
[0202] Thirty respondents were divided into groups and used the respective dosage forms of Comparative Examples 5 to 7 and Examples 4 to 6 according to the above-mentioned usage method. Afterwards, the groups exchanged the products used and answered a questionnaire survey on the tight adhesion between the teeth.
[0203] -Questionnaire answer standards-
[0204] 5 points: Gently press with your fingers, and it can be tightly integrated between the gums and teeth, making it easy to remove.
[0205] 4 points: If you press lightly with your fingers, it can fit tightly between the teeth, but the tightness of the gums is average.
[0206] 3 points: If you press gently with your fingers, it can fit tightly between the teeth, but the gums are not tightly attached.
[0207] 2 points: The adhesive force on the teeth is very strong, but the bonding force between the teeth is weak.
[0208] 1 point: The adhesive force on the teeth is very strong, but the adhesion to the gums is weak.
[0209] 2. Removal force questionnaire survey
[0210] 30 respondents pressed and used the formulations of Comparative Examples 5 to 7 and Examples 4 to 6 according to the above-mentioned usage method. Afterwards, the groups exchanged the products used and answered a questionnaire on the removal power.
[0211] -Questionnaire answer standards-
[0212] 5: It is very easy to remove and there is no residue on the teeth.
[0213] 4: Easy to remove, but leaves a little residue.
[0214] 3: It is inconvenient to remove, leaving residue and discomfort.
[0215] 2: It is inconvenient to remove and leaves a lot of residue.
[0216] 1: It is very inconvenient to remove and leaves a lot of residue.
[0217] 3. Clinical evaluation of the improvement of hypersensitive teeth or gum pain in humans
[0218] 1) Experimental subjects and usage: For Example 5 and Comparative Example 1, apply the adhesive to sensitive teeth or painful gums once a day for 10 minutes and then remove.
[0219] 2) 15 volunteers from each group with hypersensitive teeth or gum pain were selected as subjects and evaluated by questionnaire using a 5-point Likert scale after using the product for one week.
[0220] 3) Scale Standard
[0221] 5 points: The improvement effect on sensitive teeth / gum pain lasts for one month in all the areas where the sticker was applied.
[0222] 4 points: The improvement effect of sensitive teeth / gum pain is clearly felt in all the sensitive teeth / gum pain areas where the patch was applied.
[0223] 3 points: The improvement effect of sensitive teeth / gum pain is clearly felt at one or more sensitive teeth / gum pain sites where the sticker is applied.
[0224] 2 points: The sensitivity of allergic teeth to cold foods has decreased or the gum pain has decreased compared to before use.
[0225] 1 point: No improvement in hypersensitive teeth or gum pain was felt.
[0226] 4. Evaluation of the whitening effect by questionnaire on humans
[0227] 1) Experimental subjects and usage: For Examples 1, 4 and Comparative Example 2, apply the adhesive to the six middle teeth of the upper teeth once a day for 30 minutes and then remove it.
[0228] 2) 15 volunteers in each group who usually felt that their teeth were yellow and needed teeth whitening were selected as subjects. After using the product for one week, they completed a questionnaire evaluation on a 5-point Likert scale to assess the perceived whitening effect compared to the lower teeth without the product.
[0229] 3) Scale Standard
[0230] 5 points: The whitening effect of the lower teeth compared to the unbonded ones was clearly felt within five days compared to before use.
[0231] 4 points: Compared with before use, the lower teeth are obviously brighter than the unbonded ones within five days.
[0232] 3 points: After one week of use, the lower teeth are noticeably brighter than before use.
[0233] 2 points: Compared with before use, the lower teeth feel slightly brighter than the unadhered ones.
[0234] 1 point: No difference was felt compared to before use.
[0235] 5. Measurement results
[0236] Table 10 below shows the removal force and tight bonding force of the comparative example and the embodiment, and shows the improvement effect of hypersensitive teeth, the improvement effect of gingivitis, and the degree of physical perception of the whitening effect in a tabular form.
[0237]
Table 10
[0238]
[0239] [Drug release comparison experiment]
[0240] A) Operation
[0241] Pour 500mL of 0.9% sodium chloride solution into the test tube, and maintain the temperature of the test solution at 32±0.5℃ during the drug release experiment. In the absence of absorption, hindrance, or reaction, fix the embodiment or comparative example as the test object on the upper side of a disk that can be used as a sinker with the target pasting surface facing outward, and then put it into the test tube with the surface pasted with the test object facing upward, and calculate the drug release time from this moment. The disk pasted with the test object is set to be parallel to the bottom surface of the test tube and the blade of the paddle. The blade of the paddle is set to be 25±2mm away from the surface of the test object, and the number of revolutions per minute (rpm) is set to 25. When extracting the test liquid, extract 100mL of the test liquid at a certain position (a position 1cm away from the wall of the test tube between the blade of the paddle and the middle position of the test liquid surface) 30 minutes after the start of the experiment. The above drug release experiment is carried out under the conditions of a general laboratory temperature of 25℃ and a relative humidity of 65%.
[0242] B) Drug Analysis Methods
[0243] According to the drug and according to the content, select the appropriate analysis method. For example, for peroxide, select titration for analysis, for metal salts, select ICP for analysis, for natural extracts, select HPLC for analysis.
[0244] C) Results of the drug release test
[0245]
Table 11
[0246]
[0247] As can be seen from Table 11, the Example can release about 70% of the active ingredient 10 minutes after sticking. However, the Comparative Example cannot measure the degree of drug release because of the sharp increase in hardness, which makes the drug release less smooth.
[0248] [Manufacture of oral preparations]
[0249] The oral preparations of Examples and Comparative Examples having the following compositions were manufactured or purchased.
[0250]
Table 12
[0251]
[0252] Comparative Example 11: Yizhoushi TM (Parodontax TM )
[0253] Comparative Example 12: Median Enhanced Whitening Gel (Polyvinylpyrrolidone, ethanol, water, etc.)
[0254] Comparative Example 13: P&G Sensi Stop TM
[0255] The examples and comparative examples in Table 12 above were manufactured as follows.
[0256] The temperature of the ethanol solvent is raised to about 50°C. To help disperse and dissolve the polymer, a mechanical stirrer is used to dissolve the polymer while rotating at a certain rpm, especially first dissolving the polymer that is added in large quantities and requires a longer dissolution time (e.g., monoolein), and then dissolving other polymers, adding other ingredients and medicinal ingredients to prepare a uniform solution or gel.
[0257] <Evaluation of Dissolution Rate and Remaining Amount>
[0258] 1. Solubility was evaluated under hot and humid oral conditions without other physical forces.
[0259] In order to evaluate the maintenance time in a hot and humid oral cavity, 0.5 g of each of Examples 7 to 9 and Comparative Examples 8 to 12 was loaded on an artificial tooth made of a hydroxyapatite sheet (1 cm in diameter) fixed to a silicone model and placed in a constant temperature and humidity chamber at 37°C and 95% humidity, and the time required for complete dissolution was measured. Comparative Example 13 was in the form of a patch, and no separate dissolution test was performed.
[0260] 2. Evaluation of solubility in artificial saliva under the same physical force as flowing saliva
[0261] 1 g of each of Examples 7 to 9 and Comparative Examples 8 to 12 was loaded onto an artificial tooth made of a hydroxyapatite sheet (1 cm in diameter) fixed to a silicone model, and in order to evaluate the maintenance time based on saliva, the time required for complete dissolution when saliva moved from top to bottom at a rate of 1 ml / min was measured.
[0262] 3. Experimental results
[0263] Table 13 shows the results of solubility evaluation under high temperature and humid conditions without other physical forces and the results of solubility evaluation in artificial saliva to which the same physical force as flowing saliva acts.
[0264]
Table 13
[0265]
[0266] As can be seen from Table 13, the Example was not completely dissolved after 30 minutes, but the comparative example was easily dissolved.
[0267] <Panel Evaluation>
[0268] 1. Clinical evaluation of improvement of hypersensitive teeth or gum pain by questionnaire
[0269] 1) Experimental subjects and usage: For Examples 7, 9 and Comparative Examples 8, 10 to 12, apply or stick the product to sensitive teeth or painful gums once a day for 10 minutes and then remove.
[0270] 2) 15 volunteers from each group with hypersensitive teeth or gum pain were selected as subjects and evaluated by questionnaire using a 5-point Likert scale after using the product for one week.
[0271] 3) Scale Standard
[0272] 5 points: The pain relief effect lasts for one month in all areas of sensitive teeth / gum pain where the product was applied.
[0273] 4 points: The pain relief effect is clearly felt in all areas of sensitive teeth / gum pain where the product was applied.
[0274] 3 points: The pain relief effect is clearly felt at one or more sensitive tooth / gum pain sites where the product was applied.
[0275] 2 points: The sensitivity of teeth sensitive to cold foods has decreased or gum pain has decreased compared to before use.
[0276] 1 point: No improvement in hypersensitive teeth or gum pain was felt.
[0277] 2. Evaluation of the whitening effect by questionnaire on humans
[0278] 1) Experimental subjects and usage: For Example 8 and Comparative Examples 9 and 12, apply the coating to the six middle teeth of the upper teeth once a day for 30 minutes and then remove the coating.
[0279] 2) 15 volunteers in each group who usually felt that their teeth were yellow and needed teeth whitening were selected as subjects. After using the product for one week, they completed a questionnaire evaluation on a 5-point Likert scale to assess the perceived whitening effect compared to the lower teeth without the product.
[0280] 3) Scale Standard
[0281] 5 points: The whitening effect of the lower teeth compared to the unbonded ones was clearly felt within five days compared to before use.
[0282] 4 points: Compared with before use, the lower teeth are obviously brighter than the unbonded ones within five days.
[0283] 3 points: After one week of use, the lower teeth are noticeably brighter than before use.
[0284] 2 points: Compared with before use, the lower teeth feel slightly brighter than the unadhered ones.
[0285] 1 point: No difference was felt compared to before use.
[0286] 3. Evaluation results
[0287]
Table 14
[0288]
[0289] It can be seen from the above Table 14 that the preparation having the composition of the embodiment of the present invention can easily achieve the delivery of the medicinal ingredients and ensure sufficient adhesion time, thereby achieving excellent efficacy.
[0290] Industrial Applicability
[0291] The present invention provides an oral preparation that can be attached to teeth or the periphery of teeth to deliver the medicinal ingredient to the oral cavity. The present invention is a preparation for attachment to teeth or the periphery of teeth with excellent adhesion.
Claims
1. A preparation for application to teeth or tooth peripheral areas, characterized in that: The preparation for bonding to teeth or the peripheral part of teeth comprises: Medicinal ingredients for delivery into the oral cavity; phase transfer compounds; and Polymers that regulate phase transfer rates, Wherein, the phase transfer compound is ammonium alginate, potassium alginate, sodium alginate and lithium alginate or a mixture thereof. The polymer for adjusting the phase transfer rate is selected from the group consisting of polyacrylic acid, sodium polyacrylate, acrylic acid copolymer, polyquaternium-39, and copolymer of methyl vinyl ether and maleic anhydride. The above phase transfer compound and the polymer for adjusting the phase transfer rate are mixed in a weight ratio of 5:0.01 to 0.
07. After mixing the phase transfer rate regulating polymer with the phase transfer compound for 1 minute, the hardness of the preparation reaches 140 g to 350 g, and after 10 minutes, the hardness of the preparation reaches 5,200 g to 13,000 g.
2. The preparation according to claim 1, characterized in that The acrylic copolymer mentioned above is carbomer.
3. The preparation according to claim 1, characterized in that The polymer for adjusting the phase transfer rate is a copolymer of methyl vinyl ether and maleic anhydride.
4. The preparation according to claim 1, characterized in that The above formulation contains 0.01 to 10 wt % of a polymer for adjusting the phase transfer rate, relative to the total weight of the formulation.
5. The preparation according to claim 1, characterized in that The above-mentioned preparation releases 70% by weight or more of the medicinal ingredient contained in the preparation from the preparation within 15 minutes.
6. The preparation according to claim 1, characterized in that Regarding the above-mentioned preparation, an alginate selected from ammonium alginate, potassium alginate, sodium alginate and lithium alginate as a phase transfer compound and a copolymer of methyl vinyl ether and maleic anhydride as the above-mentioned polymer for adjusting the phase transfer rate are mixed, and the difference between the hardness measured after 1 minute of mixing and the hardness measured after 10 minutes is 5,000 g to 12,000 g.
7. The preparation according to any one of claims 1 to 6, characterized in that The above-mentioned active ingredient is selected from sodium fluoride, tin fluoride, indium fluoride, amine fluoride, sodium monofluorophosphate, tetrasodium pyrophosphate (TSPP), sodium acid pyrophosphate (SAPP), sodium tripolyphosphate (STP), sodium potassium pyrophosphate, tetrapotassium pyrophosphate, sodium acid metaphosphate, sodium acid polyphosphate, triclosan, chlorhexidine, Alexidine, hexetidine, sanguinarine, benzalkonium chloride, salicylanilide, domiphene, cetylpyridinium chloride (CPC), tetradecylpyridinium chloride (TPC), aspirin, ketorolac, flurbiprofen, pyro One or more of the group consisting of oxicams, meclofenamic acid, thiamine, riboflavin, niacin, pantothenic acid, pyridoxine, biotin, folic acid, vitamin B12, lipoic acid, ascorbic acid, vitamin A, vitamin D, vitamin E, vitamin K, unsaponifiable quantitative extract of corn, magnolia bark extract, myrrh, raspberry, chamomile, polyphenol sulfonate, quantitative extract of Centella asiatica, nutmeg extract, dexpanthenol, β-sitosterol, acetylsalicylic acid, zinc chloride, potassium phosphate, potassium pyrophosphate, calcium chloride, oxalic acid, potassium oxalate, and ferric oxalate.
Citation Information
Patent Citations
Continuous multi-factor authentication
KR1020160004353A
Stiffening member for recovering crack for damaged member
KR1020160012964A
Polymerizable composition for photochromic optical materials
KR1020160029820A
Delivery system for a tooth whitener using a permanently deformable strip of material
US5989569A
Delivery of hydrogel compositions as a fine mist
WO2003037276A1